The association between sustainability disclosures and the financial performance of Jordanian firms - Mohammad Jamal Azzam; Alaa Mohammad AlQudah; Ayman Ahmad Abu Haija; Mohammad Shakhatreh (Cogent Business & Management, 2020)
Researchers are paying an unprecedented level of attention to the role that sustainability disclosures may play in enhancing financial performance. This study, therefore, examines this issue in a developing country context such as Jordan using a panel data set of 1,705 firm-year observations of firms listed on the Amman Stock Exchange. Fixed effect regression with robust standard errors is used to analyse the data. The results show that, while social and governance disclosures are positively associated with financial performance, environmental disclosures do not have this association. Interestingly, when sustainability disclosures are analysed collectively, a highly positive and significant association is found between them. This study recommends that the dimensions of sustainability disclosures complement each other to enhance firms' financial performance.
Keywords: 650; environmental disclosure; social disclosure; governance disclosure; financial performance